Captura do Sistema Fluvial Camaquã pelo Sistema Fluvial Jacuí - São Gabriel, RS, Brasil - LISBOA, NELSON AMORETTI; CASTRO, JOÃO HENRIQUE WUSTROW (Pesquisas em Geociências, 1998)
The analysis of LANDSAT-MSS images and aerial photographs show a capture of headwaters of Camaquã river by Jacui river, at about 54ºW longitude and 31º latitude. This capture occurred 15 km northwest of Lavras do Sul. The area of capture has dimensions of about 30 km2. Elbows of capture and barbed tributaries of the Jacui river provide this evidence and indicate that the Camaquã river was shortened about 6 km. This capture probably has occurred in the Neogene, when erosion is belived to have started in peripheric depression of Rio Grande do Sul. Field work is needed to identify deposits that should provide more clues to the nature and timing of this capture.